The Realization of a Child Friendly City through the Fulfillment of Children's Rights and Protection - Virda Arlien Febrianthi; Isna Fitria Agustina (Indonesian Journal of Public Policy Review, 2022)
Child-friendly Regency/City Policy (KLA) is a Regency/City that has a children's rights-based development system through the integration of government, community and business commitments and resources that are planned in a comprehensive and sustainable manner in policies, programs and activities to ensure the fulfillment of children's rights. Many children's problems are still found in Sidoarjo Regency, this indicates that children's rights are still not fully fulfilled. This study aims to analyze and describe the realization of a Child Friendly City through the fulfillment of children's rights and protection in Sidoarjo Regency. The research method used is descriptive qualitative. Collecting data through observation, interviews, documentation and literature study. The results showed that the realization of a Child Friendly City in Sidoarjo Regency through the fulfillment of children's rights and protection can be seen from several programs or activities such as coordination meetings, the establishment of child-friendly sub-districts/villages, child-friendly schools, child-friendly health centers, ASI corner rooms, friendly boarding schools. children, Child Friendly Playroom (RBRA), Safe Routes to and from School (RASS), Sidoarjo children's voice formulation, PATBM, Berlian Campaign, Women and Children Protection Car (Molin), and Children's Information Car (Monik).